Explaining and Forecasting the Velocity of Money in Transition Economies, with Special Reference to the Baltics, Russia and other Countries of the Former Soviet Union. (IMF Working Papers; Working Paper, 1997)
The paper identifies a number of stylized facts on the behavior of key macroeconomic variables during high inflation and stabilization in countries in transition. To examine the extent to which these stylized facts conform to the predictions of standard open economy monetary theory, the paper develops a simple monetary model of the exchange rate incorporating price stickiness and inflation inertia, and carries out an econometric analysis of the behavior of real money balances during inflation stabilization. The paper concludes by assessing the prospects for velocity developments in countries in transition, including the likely pace of remonetization.